2017
DOI: 10.1016/j.apsusc.2016.12.093
|View full text |Cite
|
Sign up to set email alerts
|

Complementary X-ray and neutron radiography study of the initial lithiation process in lithium-ion batteries containing silicon electrodes

Abstract: A radiography cell for in operando X-ray radiography was designed and built. 2 A self-assembled CR2032 coin cell was built for in operando neutron radiography. 3 In operando X-ray and neuron radiography were conducted by using Si electrode half cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Studies range inter alia from electrolyte filling to lithiation processes and active material synthesis. [26][27][28] In the present study, we provide a direct and detailed comparison of LFP/graphite and LFMP/graphite full-cells in order to determine the influence of manganese on the initial gas evolution by means of neutron imaging (NI). Additionally, we use Prompt Gamma Activation Analysis (PGAA) to understand the long-term development of Mn dissolution and its relation to capacity retention.…”
mentioning
confidence: 99%
“…Studies range inter alia from electrolyte filling to lithiation processes and active material synthesis. [26][27][28] In the present study, we provide a direct and detailed comparison of LFP/graphite and LFMP/graphite full-cells in order to determine the influence of manganese on the initial gas evolution by means of neutron imaging (NI). Additionally, we use Prompt Gamma Activation Analysis (PGAA) to understand the long-term development of Mn dissolution and its relation to capacity retention.…”
mentioning
confidence: 99%
“…With in situ configurations, the radiography methods directly probe the working anode. Recently, by combining in situ X‐ray and neutron radiography measurements, Sun et al directly visualized the initial lithiation inside Si‐based LIBs. Many Si particles underwent no lithiation, which is in agreement with previous compositional studies .…”
Section: Applications Of Advanced Characterization Methods To Siliconmentioning
confidence: 99%
“…Earlier studies have been conducted in ex situ configurations that detected specific changes in electrode materials dissembled at different states of charge (SOCs) during the first cycle, demonstrating the buffering effect of fabricated Si–carbon (Si–C) composites on first charge/discharge capacities . Recently, by means of various advanced techniques, comparative studies of the surface properties of Si‐based materials have also been realized, and they clarified the role of the native oxides during cycling by determining a lithiation/delithiation mechanism …”
Section: Fundamental Understanding Of Fading Mechanism In Silicon‐basmentioning
confidence: 99%
“…It is a desirable idea to correlate X‐ray imaging with neutron imaging in one experiment. The conduction of X‐ray radiography and neutron radiography in battery research was firstly attempted by Sun et al [ 92 ] In their experiments, X‐ray and neutron results were used together to visualize the initial lithiation in silicon anode. Through combining the silicon morphology information provided by X‐ray imaging with the lithium distribution obtained by neutron imaging, the process was revealed that Li ions were alloyed with Si to cause the volume expansion of the Si electrode.…”
Section: Neutron Imagingmentioning
confidence: 99%